Willingness of patients with sarcoma to participate in cancer surveillance research: a cross-sectional patient survey - Kevin Jones; David Wilson; Michelle Ghert; James Hayden; Benjamin Miller; Patricia Schneider; Robert Turcotte; Roberto Velez; Victoria Giglio; Dana Ghanem; Marc Isler; Sophie Mottard; et al. (BMJ Open)
Objectives To determine the proportion of patients with extremity sarcoma who would be willing to participate in a clinical trial in which they would be randomised to one of four different postoperative sarcoma surveillance regimens. Additionally, we assessed patients’ perspectives on the burden of cancer care, factors that influence comfort with randomisation and the importance of cancer research.Design Prospective, cross-sectional patient survey.Setting Outpatient sarcoma clinics in Canada, the USA and Spain between May 2017 and April 2020. Survey data were entered into a study-specific database.Participants Patients with extremity sarcoma who had completed definitive treatment from seven clinics across Canada, the USA and Spain.Main outcome measures The proportion of patients with extremity sarcoma who would be willing to participate in a randomised controlled trial (RCT) that evaluates varying postoperative cancer surveillance regimens.Results One hundred thirty complete surveys were obtained. Respondents reported a wide range of burdens related to clinical care and surveillance. The majority of patients (85.5%) responded that they would agree to participate in a cancer surveillance RCT if eligible. The most common reason to participate was that they wanted to help future patients. Those that would decline to participate most commonly reported that participating in research would be too much of a burden for them at a time when they are already feeling overwhelmed. However, most patients agreed that cancer research will help doctors better understand and treat cancer.Conclusions These results demonstrate that most participants would be willing to participate in an RCT that evaluates varying postoperative cancer surveillance regimens. Participants’ motivation for trial participation included altruistic reasons to help future patients and deterrents to trial participation included the overwhelming burden of a cancer diagnosis. These results will help inform the development of patient-centred RCT protocols in sarcoma surveillance research.Level of evidence V.